Convergence of the positive solutions of a nonlinear neutral difference equation - Chatzarakis, G.E.; Karakostas, G.L.; Stavroulakis, I.P. (Нелінійні коливання, 2011)
Sufficient conditions are established which guarantee the convergence of the positive solutions of the
neutral type difference equation of the form ∆[x(n) − q(n)x(σ(n))] + p(n)f(x(τ1(n)), . . . , x(τk(n))) = 0,
where σ(n), n = 1, 2, . . . , are retarded arguments and τj (n), j = 1, . . . , k, are general deviated arguments. Знайдено достатнi умови збiжностi додатних розв’язкiв рiзницевого рiвняння нейтрального
типу вигляду ∆[x(n) − q(n)x(σ(n))] + p(n)f(x(τ1(n)), . . . , x(τk(n))) = 0, де σ(n), n = 1, 2, . . . , —
запiзнiлi аргументи i τj (n), j = 1, . . . , k, — загальнi вiдхиленi аргументи.